Compression of the median nerve in the carpal tunnel in a 16 year-old: A case report - Quintero, Jorge I.; Galvis, Elkin J. (Revista Colombiana de ortopedia y traumatología, 2020)
Background: Carpal tunnel syndrome is the most frequent nerve compression disorder of the upper limb. It is uncommon in children and in the majority of cases it is mainly associated with an alteration of genetic origin such as mucopolysaccharidosis. It can be of an idiopathic, traumatic, infectious origin, associated with systemic infectious diseases and occupation of the carpal tunnel. Case report: The case is presented on a 16 year-old female patient with pain in the left hand for a year, with hypoesthesia and paraesthesia of the fingertips, with no previous traumatic event. The physical examination was not conclusive, although a nerve compression disorder was highly suspected. Using electrodiagnosis and imaging, the diagnosis of carpal tunnel syndrome was made that was secondary to a ganglion identified on the floor of the tunnel. The most recommended treatment in this type of condition is surgical release and resection of the ganglion. Discussion: Carpal tunnel syndrome in children and adolescents is difficult to diagnose due to the wide range of symptoms. Once the carpal tunnel syndrome has been diagnosed, the most recommended treatment according to this cause is the surgical release of the carpal tunnel and resection of the ganglion. Carpal tunnel syndrome is an infrequent condition in children. Complementary studies should be performed to make an adequate diagnosis and an effective treatment. After the release of the carpal tunnel it rare for the neurological symptomatology to persist. Evidence Level: IV